On the Value of Commitment and Availability Guarantees When Selling to Strategic Consumers - Su, Xuanming; Zhang, Fuqiang (Management Science, 2009)
This paper studies the role of product availability in attracting consumer demand. We start with a newsvendor model, but additionally assume that stockouts are costly to consumers. The seller sets an observable price and an unobservable stocking quantity. Consumers anticipate the likelihood of stockouts and determine whether to visit the seller. We characterize the rational expectations equilibrium in this game. We propose two strategies that the seller can use to improve profits: (i) commitment (i.e., the seller, ex ante, commits to a particular quantity) and (ii) availability guarantees (i.e., the seller promises to compensate consumers, ex post, if the product is out of stock). Interestingly, the seller has an incentive to overcompensate consumers during stockouts, relative to the first-best benchmark under which social welfare is maximized. We find that first-best outcomes do not arise in equilibrium, but can be supported when the seller uses a combination of commitment and availability guarantees. Finally, we examine the robustness of these conclusions by extending our analysis to incorporate dynamic learning, multiple products, and consumer heterogeneity.